The Effectiveness of YouTube as Learning Media in Improving Learners’ Speaking Skills - Kristiani, Putu Enik; Pradnyadewi, Diah Ayu Manik (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
In language learning, speaking becomes the evidence of students’ competence of the language that is learnt. However, students’ speaking ability can be inhibited by several problems that are faced such as lack of confidence, lack of vocabulary and grammar, and inappropriate teaching strategy. In this era, the developments of information and technology (IT) can be the solution of those problems. The development of technology seems to have many positive effects on education. Technology provides a variety of learning media that is fun for students. One of the technological developments that can be used as learning media is YouTube. YouTube provides various types of videos related to learning. In learning English, EFL learners can find various types of videos that can help the learning process. Therefore, YouTube can help learners to improve their language skill, especially their speaking skills. The aim of this paper is to explain the effectiveness of using YouTube as learning media in improving learner’s speaking skills